Rapid identification of the NAT2 genotype in tuberculosis patients by multicolor melting curve analysis. (July 2016) - Hu, Yanjie; Chen, Suting; Yu, Xia; Dai, Guangming; Dong, Lingling; Li, Yunxu; Zhao, Liping; Huang, Hairong
Aim: NAT2 genotype is an indicator for isoniazid dosage adjusting for tuberculosis treatment. Multicolor melting curve analysis (MMCA) was evaluated as a potential method for NAT2 genotyping.Materials & methods: 352 blood samples were analyzed by MMCA kit (Zeesan Biotech Co., Xiamen, China) targeting NAT2 SNPs at T341C, C481T, G590A and G857A, and direct sequencing was used as control.Results: The sensitivity, specificity and accuracy of the MMCA assay for rapid NAT2 genotype detection were 97.9, 99.6 and 99.1% respectively, whereas for intermediate genotypes the values were 99.5, 98.7 and 99.1%, respectively, and for slow genotypes the values were 100% for the three aspects. The 24 saliva and blood for the control samples were also successfully analyzed using the MMCA assay, both produced uniform outcomes.Conclusion: The MMCA assay described in our study is very promising for the efficient determination of NAT2 genotype, and can facilitate the personalized dosing of isoniazid.